PENGARUH PENAMBAHAN TRACE METAL FE TERHADAP PENYISIHAN KANDUNGAN PADATAN LIMBAH CAIR KELAPA SAWIT MENGGUNAKAN REAKTOR HYBRID UPFLOW ANAEROBIC SLUDGE BLANKET - Julika Sitinjak, Janwarisman Purba, Fatimah (Jurnal Teknik Kimia USU, 2014)
Research about influence the addition of trace metal Fe against allowance for the solid content of palm oil mill effluent using Hybrid Upflow Anaerobic Sludge Blanket Reactor aim to know the additionof trace metal Fe against allowance for the solid content of palm oil mill effluent using HUASB reactor based on removal of Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) dan Volatile Suspended Solid (VSS). The reactor isa reactor with a combination of suspended growth reactor in the bottom and attached growth reactor at the top. The material used is palm oil mill effluent and inoculum derived from PKS Pagar Merbau. Test parameters to observed are COD, TSS and VSS. The optimum conditions obtained on the organic load is 17024 mg/l with the addition of Fe is 0.5 mg/l so that obtained COD reduction is 85.891%, TSS reduction is 86.047% and VSS reduction is 36.566%.